Application of machine learning in the classification of area potential for transaction forecasting using regression analysis in two regions of the Johannesburg conurbation - Masola, Kabelo Charles (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.